Grape Flavonoid Evolution and Composition Under Altered Light and Temperature Conditions in Cabernet Sauvignon (Vitis vinifera L.) - Blancquaert, Erna H.; Oberholster, Anita; Ricardo-da-Silva, Jorge M.; Deloire, Alain J. (Frontiers in Plant Science, 2019)
The evolution of flavan-3-ols under altered temperature and light conditions in the fruit zone were followed in Cabernet Sauvignon (Vitis vinifera L.) grapes during ripening. The study was conducted over two consecutive seasons 2010/2011 and 2011/2012 comprising two main treatments in which the light quantity was manipulated in the bunch zone: 1) standard (STD) with no lateral shoot or leaf removal and 2) Leaf Removal West (LRW) treatment with leaf removal on the western side of the bunch zone. Furthermore, the light quality was altered by installing ultra-violet-B suppressing sheets within the bunch zone in both seasons. Tannin evolution was dependent on the prevailing light quality/quantity and temperatures during berry development in a particular season. Grape seed tannin accumulation coincided with seed development and commenced at the early stages of berry development. Seed proanthocyanidin composition were not influenced by the treatments. The largest impact on proanthocyanidin accumulation and structure in the skin was due to seasonal variations highlighting the complex interaction between light quality and/or quantity across the two growing seasons and eventually the complex interaction with temperature. Flavonol accumulation was significantly influenced by the light quality, which is known to be the main abiotic driver of flavonol biosynthesis regulation. Anthocyanin concentration and content were largely dependent on the temperature and light quality in a particular season. Anthocyanin composition was altered by the season rather than the treatment.